Establishing the financial reporting of cryptocurrency in light of existing International Reporting - Mezbah Uddin Ahmed, Moutaz Abojeib, (Opción, 2019)
The objective of this research is to establish the appropriate financial reporting classification of cryptocurrency in light of existing International Financial Reporting Standards (IFRS) via qualitative comparative research method. This research analyses Bitcoin based on five different viewpoints, namely cash, cash equivalent, financial asset, inventory, and intangible asset. The research identifies the applicable IFRS requirements and compares those with Bitcoin characteristics. The research concludes by proposing the most appropriate classification and disclosure recommendations that the local and international standard setters can take into account in developing financial reporting requirements for cryptocurrency.